Here Today Gone Tomorrow: Conceptualizing Instructional Leadership Through Case Studies of Unsustained Initiatives. (May 2015) - Shulman, Vivian; Sullivan, Susan
This study examines two case studies of failed leadership in school-based professional development. We describe the two initiatives and look to current leadership theories to help account for the events that occurred. The sociologist Bourdieu's concept of habitus offers an approach to understanding the relationship between individual agency and structural determinism. Chaos and complexity theory conceptualize organizations from a systems level where relationships and connections among all constituents—both inside and outside—are the focus. In addition, transformational and charismatic leadership theories allow for a consideration of leadership characteristics. While much can be learned from failed attempts, a comparative analysis of failed and successful strategies may assist leaders in avoiding the pitfalls of these challenging times while simultaneously providing strategies for success.